Management of hemodialysis unit in a specialized hospital - Sultana, Arifa; Saha, Ashees Kumar; Bilkis, Afsana; Sultana, Papia; Khatun, Sajeda; Hossain, Kazi Jahangir (Asian Journal of Medical and Biological Research, 2021)
Chronic Kidney disease is becoming a global public health problem throughout the world. The aim of the study was to assess management status of the hemodialysis unit in a specialized hospital. It was a hospital based descriptive cross sectional study. A total of 17 participants were selected by purposive sampling method on the basis of defined selection criteria from January 2015 to December 2016. The place of study was National Institute of Kidney Diseases and Urology (NIKDU) hospital, Dhaka. The research instruments were a semi structured questionnaire and a checklist. The socio-demographic status of the respondents showed that 11.8 %( n=02) were doctor, 58.8 %( n=10) nurses and 29.4 %( n=05) were technician. Mean age of care providers was 38.82±8.79 years. Majority of respondents, were satisfied regarding the unit including physical facilities 76.5% (n=13) cleanliness of the unit 58.8% (n=10) and medical record facility 52.9% (n=9). Need to strengthen infection control measure and BCC activities among the service providers to improve the management status of the hemodialysis unit of NIKDU hospital. Asian J. Med. Biol. Res. December 2020, 6(4): 683-688